Impact of pediatric anesthesia management on cancer outcomes in children—a narrative review - Fenelon, Aileen; Hauser, Neil; von Ungern-Sternberg, Britta S. (Frontiers in Oncology, 2025)
ImportanceThe relationship between anesthetic technique and pediatric oncological outcomes is an emerging field of interest. With significant improvements in childhood cancer survival in recent decades, there is an increased focus on optimizing the quality of survival and reducing the incidence of metastasis and recurrence. The aim of this narrative review article is to investigate and consolidate the current available evidence assessing the immunomodulatory effects of anesthesia in the pediatric oncology population.ObservationsThere is mounting evidence supporting an association between perioperative interventions such as anesthetic techniques and oncological outcomes in adults. Research, predominantly based on laboratory studies and retrospective studies in the adult population, has explored this association, often with mixed results. Some studies found that agents such as volatile anesthetics promoted cancer cell dissemination or recurrence by altering tumor microenvironments, while others argued that the influence of anesthesia on cancer recurrence is minimal and emphasized the need for further, more targeted research.Conclusions and relevanceThe significant differences which exist between adult and pediatric oncology populations, in terms of immune system maturation, underlying malignancy, treatment regimens, and frequency of anesthetic exposure, present a further challenge in applying the findings from the current, mainly adult-based evidence to pediatric anesthesia practice. Evidence suggests a trend toward an effect rather than a definitive answer. A large, high-quality randomized, controlled trial is warranted to further our understanding of the effects of anesthesia in pediatric oncology patients.